#SaveJanda Movement: Countering Social-Stigma - Syarifah Nur Aini; Febriansyah Kulau; Awanis Akalili (Prodi Ilmu Komunikasi UTM, 2025)
The development of digitalization makes activities in cyberspace increasingly massive and have a big impact on society. Today's society does not only depend on face-to-face efforts, but orientation and actualization activities can be carried out online. The Save Janda community presents social media Instagram @save_janda as a space to build positive narratives that are often stigmatized and negatively labeled by society. This research answers the question of how digital activism in the #SaveJanda Movement on the Instagram account @save_janda can overcome this. social stigma against widows in Indonesia? This research uses a critical paradigm with a qualitative approach and qualitative content analysis techniques. The content of the @save_janda Instagram account studied is content throughout 2023 from January to September with a total of 14 contents. This research focuses on content uploaded using the hashtag #SaveJanda via the Instagram account @save_janda. The @savejanda account is interesting to research because it shows the struggle of widowed women against the bonds of patriarchal culture and shows their empowerment. What emerges is how the hashtag #SaveJanda which is part of Instagram is used by the public to fight negative narratives about widows. Various types of content are presented to provide information, create empathy and sympathy, as well as carry out positive constructions in the form of (a) productivity and concern for others, (b) the phenomenon of patriarchal logic in society, to (c) self-empowerment as a woman.